PENGARUH MODEL PENERAPAN OMNIMBUS LAW TERHADAP POLITIK HUKUM DI INDONESIA - Muslim, Dendi Ramdani; Rizkia , Nabila Subur; Mufti , Rizal Agung; Rosidin , Utang (Gapenas Publisher, 2024)
Omnibus law is a decission of the President Joko Widodo to overcome the problems of the complexity of licensing and overlapping regulations that can impede investment. The omnibus law is made in the form of legislation that it is formed based on the provisions of the regulation of legislation. Omnibus law that will be made there are 3 (three) of the bills on employment, tax bill, and community empowerment bill. The Omnibus Act will replace part or all of the current legislation and is associated with the cluster of the Omnibus Act. Obstacles faced in the formation of the Omnibus Act is still not a member of the House of Representatives in drafting the omnibus Act so the need for special attention and the solid agenda of the members of the House of Representatives can be a factor of the death of the establishment of the Omnibus law